Home range and activity patterns of Sunda scops owl in Peninsular Malaysia - Zolkanain, Nornajmi Hanis; Puan, Chong Leong; Hussin, Mohamed Zakaria; Md. Sharif, Badrul Azhar (Raffles Museum of Biodiversity Research, 2016)
The Sunda scops owl Otus lempiji is commonly found in many wooded habitat types in Malaysia. However, as with other owl species in Southeast Asia, there is a lack of published ecological studies. We examined the home range and activity patterns of six adult Sunda scops owls based on radio-telemetry in an isolated forest, namely Ayer Hitam Forest Reserve, Selangor, Peninsular Malaysia from December 2012 to June 2013. Mean minimum convex polygon and harmonic mean home range areas of the owls were 2.40 ± 0.28 SD ha and 4.00 ± 0.78 SD ha, respectively. The birds exhibited territorial behaviour with little overlapping of home ranges. Movements (the means of inter-fix speed) were not associated with lunar illumination nor with time. This study provided baseline information on the spatial requirements of the Sunda scops owl in a lowland forest.